2019
DOI: 10.1021/acscatal.9b04689
|View full text |Cite
|
Sign up to set email alerts
|

Role of Boron in Enhancing the Catalytic Performance of Supported Platinum Catalysts for the Nonoxidative Dehydrogenation ofn-Butane

Abstract: Platinum-based supported catalysts for hydrocarbon conversion are among the most effective for selective dehydrogenation and isomerization processes. However, high process temperatures and the possibility of coke formation require catalyst modifications to mitigate such effects. One of the emerging approaches to prevent platinum catalyst deactivation is the use of boron additives that have been proposed to prevent coking. Despite such a valuable property of boron, the mechanisms for extending the catalyst life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 83 publications
4
34
0
Order By: Relevance
“…The results showed that the presence of boron improves the catalyst stability for non-oxidative dehydrogenation of n-butane. Also, the rate of n-butane conversion over Pt/B/SiO 2 was found to be more than two times better as when using Pt/SiO 2 , throughout the duration of the reaction (25 h) [62].…”
Section: Coke Formation and Catalyst Deactivationmentioning
confidence: 87%
See 2 more Smart Citations
“…The results showed that the presence of boron improves the catalyst stability for non-oxidative dehydrogenation of n-butane. Also, the rate of n-butane conversion over Pt/B/SiO 2 was found to be more than two times better as when using Pt/SiO 2 , throughout the duration of the reaction (25 h) [62].…”
Section: Coke Formation and Catalyst Deactivationmentioning
confidence: 87%
“…Pt-based catalysts on various supports are among the most effective catalysts for selective dehydrogenation and isomerisation processes. However, high process temperatures and the possibility of coke formation require catalyst modifications to mitigate such effects [62]. Such catalysts were studied by Byron et al with Pt/B/SiO 2 [62], Silvestre-Albero et al with Pt-Zn/X-zeolite [63] and Casanave et al with Pt-In [64].…”
Section: Coke Formation and Catalyst Deactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the combination of late and post-transition metals a recent study by Teplyakov et al utilizes the SOMC approach to combine Pt and B supported on SiO 2 for butane dehydrogenation. 122 The material was synthesized via sequential grafting of B(OiPr) 3 and [(MeCp)PtMe 3 ] onto partially dehydroxylated SiO 2 with an intermediate calcination step at 400 °C. A treatment under H 2 yielded 2.6 nm monometallic Pt particles supported on B doped SiO 2 as evidenced by HAADF-STEM and HR-TEM.…”
Section: Modelling Alkane Dehydrogenation Catalysts Using Supported Metal Nanoparticles and Alloys Prepared Via Somcmentioning
confidence: 99%
“…In order to find suitable materials, research efforts have concentrated on the use of post transition metal or main group element promoters like Zn [6][7][8][9][10][11][12][13] , B 14,15 , Ga [16][17][18][19][20] , In [21][22][23] and Sn 1,5,24 in combination with varying supports. All these promoters are known to drastically increase the PDH performance compared to monometallic Pt by increasing both selectivity and stability.…”
Section: Introductionmentioning
confidence: 99%